Effect of an injectable trace mineral at the initiation of a 14 day CIDR protocol on heifer performance and reproduction(1) - Stokes, R. S. (Transl Anim Sci, 2017)
Three experiments were conducted at separate locations to determine the effects of a trace mineral injection (TMI), Multimin 90, on heifer performance and reproduction. In Exp. 1, [spring-born, Angus, n = 93, body weight (BW) = 428 ± 45.2 kg], Exp. 2 (spring-born, Angus × Simmental, n = 120, BW = 426 ± 54.0 kg), and Exp. 3 (fall-born, commercial Angus, n = 199, BW = 345 ± 39.7 kg) heifers were stratified by BW within experiment and assigned to 1 of 2 treatments: a control, saline injection, or TMI at a dose of 1 mL/68 kg BW. Free choice mineral, containing Cu, Mn, Se, and Zn formulated to meet or exceed NRC recommendations, was supplemented to heifers. Injections were given 33 d prior to breeding at the initiation of a 14-d controlled internal drug release (CIDR)-prostaglandin protocol. There was no difference (P ≥ 0.37) in BW during Exp. 1. Additionally, there was no difference (P ≥ 0.52) in body condition score (BCS) at initiation or at artificial insemination (AI) and final pregnancy confirmation in Exp. 1; however, a greater (P = 0.03) BCS was noted for control heifers at breeding. Pregnancy rates to timed AI and overall pregnancy rates were also similar (P ≥ 0.74) regardless of treatment. During Exp. 2, BCS and BW did not differ (P ≥ 0.44) across treatments. There was a tendency (P = 0.07) for TMI heifers to have an increased AI pregnancy rate (62 vs. 45%) compared with control heifers despite no difference (P = 0.51) in overall pregnancy rate. In Exp. 3, BW was not different (P ≥ 0.39) across all time points. Also, BCS did not differ (P ≥ 0.45) at initiation, AI, or final pregnancy conformation. Interestingly, there was a tendency (P = 0.10) for TMI heifers to have an increased BCS at the time of breeding compared with control heifers. However, there were no differences (P ≥ 0.50) in AI and overall pregnancy rates. In 1 of 3 experiments, an injectable trace mineral administered 33 d prior to the breeding season in conjunction with a 14-d CIDR protocol, tended to increased AI conception rates of heifers even when adequate trace mineral supplement was provided. The variable response observed across experiments may be caused by differences in breed, calving season, mineral sources, and management strategies.